Young people and romantic love: a review of the impact of myths on intimate relationships and on the tolerance and normalization of violence (Jóvenes en la Ciencia, 2026)
The objective of this documentary review is to analyze the findings of research related to the impact that myths about romantic love have on young people's relationships, facilitating the development of intervention programs for young people, preventing different types of violence against partners, and promoting good-quality relationships. Twenty-seven studies published between 2015 and 2025 were reviewed in databases such as PubMed, SCielo, and Redalyc, as well as the Jane search engine. The results included research conducted on populations of different nationalities and ages ranging from 14 to 30 years old. Seven myths were found to be the most relevant, each linked to certain ages, as well as a relationship between each of them and the presence of violence. Starting from the concept of love and gender roles, the myths of romantic love are determined, which together affect how couple relationships are established, most of which are poor quality relationships that jeopardize the well-being of one or both people, and even the perception of the problem, in some cases clearly identified and in others normalized and accepted by their own way of thinking.